Factors Influence Tadris English Students' Language Ability - Hamzah Alias (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
The main objective of this study is to identify the variables that affect the command of English of Tadris English students. This study uses a qualitative method and is descriptive. Tadris English students at the As'adiyah Sengkang Islamic Institute served as the research's informants. Two methods of gathering data were conducted: interviews and documentation. Using data gathering techniques, data reduction, data presentation, and conclusion are the steps in the data analysis process. Veracity testing is done using three different sources and approaches. According to the research's findings, the following variables affect students' proficiency in the English language: 1) Listening skills: children in this instance have a limited vocabulary and lack focus. 2) Students' limited vocabulary and reading motivation are elements that affect their reading abilities. Speaking ability, in this instance, is determined by students' lack of confidence and their inability to grasp the majority of grammatical constructions. 4) Poor writing proficiency, low interest, and a lack of support from their surroundings are issues that affect students.